2015
DOI: 10.1186/s13065-015-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

An improved kilogram-scale preparation of atorvastatin calcium

Abstract: BackgroundIf literature protocols are followed, conversion of an advanced ketal ester intermediate (available in kilogram quantities via a published Paal-Knorr synthesis) to cholesterol-lowering drug atorvastatin calcium is hampered by several process issues, particularly at the final stage where the hemi-calcium salt is obtained.ResultsWe developed a high-yielding synthesis of atorvastatin calcium salt on 7 kg scale that affords >99.5% product purities by introducing the following key improvements: i. isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Interestingly, initial indications suggested that Yb(OTf) 3 3 in EtOH at 40 C provided the crude enaminone 203, which was taken directly into the next step where it was subjected to a high-speed vibration milling at 20 Hz for 1 h together with 204, 1 mol% Yb(OTf) 3 , and AgNO 3 (1 equiv.). Acetonide-protected atorvastatin tert-butyl ester 177 was then isolated at 40% yield and was readily converted to atorvastatin lactone 156 at 94% yield, using HCl in MeOH at room temperature for 3 h. A detailed description of an improved kilogram-scale synthesis of atorvastatin calcium 186 was reported by Novozhilov and coworkers [124]. Their route started from the acetonide-protected tert-butyl ester of atorvastatin 177 on a 7-kg scale.…”
Section: Scheme 35mentioning
confidence: 99%
“…Interestingly, initial indications suggested that Yb(OTf) 3 3 in EtOH at 40 C provided the crude enaminone 203, which was taken directly into the next step where it was subjected to a high-speed vibration milling at 20 Hz for 1 h together with 204, 1 mol% Yb(OTf) 3 , and AgNO 3 (1 equiv.). Acetonide-protected atorvastatin tert-butyl ester 177 was then isolated at 40% yield and was readily converted to atorvastatin lactone 156 at 94% yield, using HCl in MeOH at room temperature for 3 h. A detailed description of an improved kilogram-scale synthesis of atorvastatin calcium 186 was reported by Novozhilov and coworkers [124]. Their route started from the acetonide-protected tert-butyl ester of atorvastatin 177 on a 7-kg scale.…”
Section: Scheme 35mentioning
confidence: 99%
“…One example is in the commercial ton-quantity preparation of an anti-cholesterolemic drug, atorvastatin (Lipitor), as illustrated by the condensation of diketone 8 and amine 9 to afford pyrrole 10 (Scheme 3). 16 …”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of an improved kilogram-scale synthesis of atorvastatin calcium 186 was reported by Novozhilov and coworkers [124]. Their route started from the acetonide-protected tert-butyl ester of atorvastatin 177 on a 7-kg scale.…”
mentioning
confidence: 98%